2009
DOI: 10.1088/0022-3727/42/3/035009
|View full text |Cite
|
Sign up to set email alerts
|

Giant inverse magnetocaloric effect near room temperature in Co substituted NiMnSb Heusler alloys

Abstract: The effect of Co on the structural, magnetic and magnetocaloric effect (MCE) of Ni 50-x Co x Mn 38 Sb 12 (x=0,2,3,4,5) Heusler alloys was studied. Using x-ray diffraction, we show the evolution of the martensitic phase from the austenite phase. The martensitic transition temperature is found to decrease monotonically with Co concentration. Remarkable enhancement of MCE is observed near room temperature upon Co substitution. The maximum magnetic entropy change of 34 Jkg -1 K -1 was achieved in x=5 at 262 K in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 22 publications
5
67
0
Order By: Relevance
“…Hence, this can be termed an inverse MCE. There are reports wherein giant inverse MCE has been observed in alloys like NiMnSb Heusler alloys [28,29]. A positive entropy change has been recently reported in zinc ferrite nanoparticles [30].…”
Section: Mce Measurementsmentioning
confidence: 95%
“…Hence, this can be termed an inverse MCE. There are reports wherein giant inverse MCE has been observed in alloys like NiMnSb Heusler alloys [28,29]. A positive entropy change has been recently reported in zinc ferrite nanoparticles [30].…”
Section: Mce Measurementsmentioning
confidence: 95%
“…Recently, we have reported a large enhancement of MCE with Co substitution in NiMnSb. 18 In this paper, we report the effect of pressure on the magnetic and MC properties of Ni 50−x Co x Mn 38 Sb 12 . It was found that the substitution of Co for Ni reduces the martensitic transition temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The magnetic properties in this system are mainly due to Mn magnetic moment as Ni moment is negligible. The Mn-Mn indirect exchange interaction (RKKY type) plays the key role behind the observed magnetic behavior in this system.…”
mentioning
confidence: 95%
“…In the NiMnSb bulk system, MCE and MR properties has been studied extensively. 2,3,[5][6][7][8] Recently melt spinning technique has gained much attention as it produces strongly textured polycrystalline ribbons. There are various reports on crystallographically textured melt spun ribbons where magnetic anisotropy plays the vital role in determining the observed properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation